Rapid antimicrobial susceptibility of Enterobacteriaceae by disk diffusion directly from blood culture bottles using the EUCAST RAST breakpoints. (September 2020) - Martins, Amanda; Wink, Priscila; Pereira, Dariane; Souza, Andria; Aquino, Valerio; Barth, Afonso
Highlights: Early readings of AST presented appropriate results only using RAST breakpoints. Optimal early reading varied according to species. RAST at 6h presented an almost perfect PABAK classification for all antimicrobials. Early readings in 6h using the RAST breakpoints may be used. Abstract: Objectives: To evaluate the disk diffusion technique after 4 and 6 h directly from positive blood culture bottles of Enterobacteriaceae using the rapid antimicrobial susceptibility test (RAST) breakpoints established by The European Committee on Antimicrobial Susceptibility Testing (EUCAST). Methods: A total of 61 isolates of Escherichia coli and Klebsiella spp. were selected. The results were assessed using the RAST breakpoints (4–6 h) as well as the standard breakpoints (18 h) from EUCAST. Results: The vast majority of the zone diameters of E. coli and Klebsiella spp. were optimally readable after 6 h of incubation. RAST at 6 h presented best results of categorical agreement (CA) and errors (CA = 94.4%, minor errors [mE] = 4.3%, major errors [ME] = 0.8% and very major errors [VME] = 0.4%) compared to RAST at 4 h (CA = 84.3%, mE = 13.0%, ME = 3.2% and VME = 0.4%). The proportion of results in the area of technical uncertainty decreased over time: from 13.8% at 4 h to 6.8% at 6 h. According to the U.S. Food and Drug Administration and ISO criteria, early readings at 6 h using the RAST breakpoints provided acceptable results (CA > 90%), whereas accuracy of results at 4 h was unacceptable (CA < 90%). Conclusion: These data indicate that the early readings at 6 h using the RAST breakpoints for all antibiotics tested in this study (except amikacin) may be used in the clinical microbiology laboratory to anticipate the antimicrobial susceptibility test results of blood cultures. Early readings at 4 h (RAST breakpoints) may also be used, but not for all antibiotics.